2002
DOI: 10.1080/08989620210354
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent for Research on Stored Blood and Tissue Samples: A Survey of Institutional Review Board Practices

Abstract: Numerous position papers have outlined informed consent recommendations for the collection, storage, and future use of biological samples; however, there currently is no consensus regarding what kinds of information should be included in consent forms. This study aimed to determine whether institutional review boards (IRBs) vary in their informed consent requirements for research on stored biological samples, and whether any variation observed could be correlated to factors such as volume of work, IRB members'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The Office for Human Research Protections in the US Department of Health and Human Services released guidance for research involving coded private information and biological specimens [10]. High variability between IRBs in regard to review of genetic studies has been demonstrated [11, 12] and draft templates have been proposed to facilitate standardization of written informed consent documents for genetic research and DNA banking [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…The Office for Human Research Protections in the US Department of Health and Human Services released guidance for research involving coded private information and biological specimens [10]. High variability between IRBs in regard to review of genetic studies has been demonstrated [11, 12] and draft templates have been proposed to facilitate standardization of written informed consent documents for genetic research and DNA banking [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…This profusion of guidance has led to divergent practices,1 2 with one study finding that institutional review boards in the United States recommend “various consent options, all of which are different.”3 Such variation may undermine the scientific value of patients' contributed samples and greatly increase the costs of such research. Assessing whether people's views support one of the recommended options for consent could provide a solution to these problems.…”
mentioning
confidence: 99%
“…86−89 Institutional review boards may therefore lack consistent methods for evaluating informed consent forms, confidentiality protections, and other protocol elements. 96 Another set of ethical issues concerns whether and how new applications should be introduced clinically. It will require considerable research funding and many years to gather detailed information about the psychosocial and medical outcomes of genetic counseling and testing for specific psychiatric disorders.…”
Section: Genetics and The Ethics Of Emerging Technologiesmentioning
confidence: 99%